A susceptibility locus for lung cancer maps to nicotinic acetylcholine receptor subunit genes on 15q25. - HEALY, CLAIRE (My University, 2008)
Abstract: Lung cancer is the most common cause of cancer death worldwide, with over one million cases annually(1). To identify genetic factors that modify disease risk, we conducted a genome- wide association study by analysing 317,139 single- nucleotide polymorphisms in 1,989 lung cancer cases and 2,625 controls from six central European countries. We identified a locus in chromosome region 15q25 that was strongly associated with lung cancer ( P= 9 x 10(-10)). This locus was replicated in five separate lung cancer studies comprising an additional 2,513 lung cancer cases and 4,752 controls ( P = 5 x 10(-20) overall), and it was found to account for 14%( attributable risk) of lung cancer cases. Statistically similar risks were observed irrespective of smoking status or propensity to smoke tobacco. The association region contains several genes, including three that encode nicotinic acetylcholine receptor subunits ( CHRNA5, CHRNA3 and CHRNB4). Such subunits are expressed in neurons and other tissues, in particular alveolar epithelial cells, pulmonary neuroendocrine cells and lung cancer cell lines(2,3), and they bind to N'- nitrosonornicotine and potential lung carcinogens(4). A non- synonymous variant of CHRNA5 that induces an amino acid substitution ( D398N) at a highly conserved site in the second intracellular loop of the protein is among the markers with the strongest disease associations. Our results provide compelling evidence of a locus at 15q25 predisposing to lung cancer, and reinforce interest in nicotinic acetylcholine receptors as potential disease candidates and chemopreventative targets(5).
PUBLISHED
Keywords: FAGERSTROM TOLERANCE QUESTIONNAIRE; GENOME-WIDE ASSOCIATION; HAPLOTYPE MAP; DEPENDENCE